Case study of the symbolic interpretivism in a r&d unit and its influence on the decision to outsourcing its activities - Schreiber, Dusan (Revista de Administração da UFSM, 2018)
The innovation, both technological and organizational, are no longer a fad, occupying a prominent place within organizations. With the opening of markets and sophistication of the standard requirements of consumers, both domestically as abroad, differentiation has become a slogan and innovation a necessity. Within the technological innovation activities of research and development are considered essential and deserves an increasingly attention of researchers. Traditionally regarded as a highly technical sector, with a focus on designing solutions technologically and commercially viable, R&D assumed new responsibilities, which implied a change of its profile, more fit to interact with other organizational units. This process implied, too, in the expansion of the symbolic universe of the group of experts that works in the R&D sector, with inclusion in its repertoire new values and images of the organization, represented in the decision-making process. The article analyzes the case of company BETA, a technology-based company, located in the metropolitan area of Porto Alegre, in order to understand social network that enhance the symbolic interpretation of technicians that work in the R & D sector, as to identify if and how this interpretation may influence decision about how to perform the activities of the technological research.